Managing Outpatient Cycle Times in Hospitals Using Integrated Closed-Loop Approaches - Ganesh-Babu B Subburaman; Jyoti R Munavalli; Thulasiraj Ravilla; Helen Mertens; Carroll Webers; Shyam Vasudeva Rao; Frits van Merode (SAGE Publishing, 2023)
Long waiting times in outpatient clinics have multiple adverse effects on patients and their attendants, staff and hospital management. Several approaches practiced to manage the cycle time have been proposed. The purpose of this study was to evaluate the impact of implementing closed-loop based multiple approaches together. This study was conducted in Aravind Eye Hospital (AEH), Madurai, India where several approaches to manage cycle times have been implemented over the years. Scheduling system was introduced to manage COVID-19 specific norms. We compared the cycle times in general outpatient clinics in a regime in which multiple approaches were practiced together before and after introducing scheduling to regimes in which individual approaches were practiced. We analysed how the cycle time varied by patient load. Cycle time for all patient days when the combined approach was used was 19% lower than baseline, and better than under each of the individual approaches. The outcome sustained even during the COVID-19 pandemic that necessitated additional processes and procedures. Therefore, implementing multiple approaches can be more effective to reduce the cycle time than implementing individual approaches